2019
DOI: 10.3390/pharmaceutics11040191
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study of the Influence of Curcuma longa Extracts on the Microbiota Modulation Process, In Patients with Hypertension

Abstract: The multiple causes of cardiovascular diseases signify a major incidence and developmental risk of this pathology. One of the processes accountable for this pathologic development is the instauration of dysbiosis and its connection with an inflammatory process. Low antioxidant colonic protection encourages the progression of inflammation, with cardiovascular dysfunctions being a secondary consequence of the dysbiosis. Curcumin is one of the bioactive compounds displaying promising results for the reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 43 publications
0
35
0
1
Order By: Relevance
“…The claim is justified by increasing the amount of CO 2 formed, which can support the use of the carbon source (data unpublished as of yet), by probiotic yeasts (S. cerevisiae and S. boulardii). This aspect has been demonstrated by previous studies that have shown the selective use, by certain strains, of bioactive components in extracts [29,52]. Increasing the number of favorable strains in the microbial pattern of the microbiota can thus have two causes, as detailed below:…”
Section: Probiotics Strains and Bioavailability Of Functional Compoundsmentioning
confidence: 86%
See 4 more Smart Citations
“…The claim is justified by increasing the amount of CO 2 formed, which can support the use of the carbon source (data unpublished as of yet), by probiotic yeasts (S. cerevisiae and S. boulardii). This aspect has been demonstrated by previous studies that have shown the selective use, by certain strains, of bioactive components in extracts [29,52]. Increasing the number of favorable strains in the microbial pattern of the microbiota can thus have two causes, as detailed below:…”
Section: Probiotics Strains and Bioavailability Of Functional Compoundsmentioning
confidence: 86%
“…They differently modulate the microbiota, favoring the development of some bacterial strains, and act like a prebiotic. A recent study revealed that the Curcuma longa extract with a high curcumin content (Table 1) modulates the microbiota of patients with hypertension by improving the ratio of SCFAs, which strongly influences the Enterobacteriaceae group and negatively influences the Bacteroides-Prevotella-Porphyromonas groups [29]. Polyphenols from the Lonicera caerulea L. berry reduced the Firmicutes/Bacteroidetes ratio in the fecal microbiota of a mouse model with an induced high-fat diet (HFD) and increased the relative abundance of Bacteroides and Parabacteroides.…”
Section: Gut Microbiota and Polyphenolsmentioning
confidence: 99%
See 3 more Smart Citations